The Effect of Competence, Work Discipline, and Workload on Employee Performance at PT. Anugerah Pharmindo Lestari - Zul Arisman Siddik; Samrin Samrin; Teguh Wahyono (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of competence, work discipline, and workload on employee performance at PT Anugerah Pharmindo Lestari. The research focuses on examining the influence of these independent variables on employee performance both partially and simultaneously. This study employs a quantitative approach using a survey method. Research data were collected through the distribution of questionnaires to 45 employees as respondents. The data analysis techniques used include descriptive statistics to describe data characteristics, classical assumption tests as prerequisites for analysis, and multiple linear regression analysis. Hypothesis testing was conducted using the t-test to determine partial effects and the F-test to determine simultaneous effects among variables, with the support of statistical data processing software. The results indicate that competence has a positive but not significant effect on employee performance. Work discipline has a positive and significant effect on employee performance and is identified as the most dominant variable. Workload has a negative but not significant effect on employee performance. Simultaneously, competence, work discipline, and workload have a significant effect on employee performance, indicating that these three variables collectively explain variations in employee performance. This study is limited by a relatively small number of respondents and a research scope confined to a single company. In addition, the variables examined are still limited and do not include other factors that may influence employee performance. The findings of this study are expected to contribute to the development of human resource management knowledge and to serve as a reference for companies in improving employee performance through effective work discipline management.